Examining the Importance of Context Education in the Translation Process (A Descriptive Analytical Study) - Eltigani, Mohammed Abdulaziz; Ibrahim , Ishaq; Al-Khayyat, Mustafa; Ibrahim, Rabie (Cadernos de Educação Tecnologia e Sociedade, 2024)
The purpose of this research was to investigate the importance of context education in the translation process (a descriptive analytical study). The article proves in six research points that translation is a practice that goes beyond the linguistic field to the cultural background and critical context in the processes of understanding and interpretation, in such a way that it is with the main goals of the intended text. Therefore, this research with a descriptive and analytical method that has reached several results claims that the work of translation is not correct without the interpretation capabilities that the translator must have with the background knowledge and awareness of the linguistic characteristics and cultural differences of the two languages. which represents the tools that help the translator to obtain the translated correspondence of the original text after finding the context and its many aspects in which the text exists. Therefore, according to the results of the research, we conclude that in learning and teaching a foreign language, it is recommended that students' linguistic experiences be raised to encourage them to know how to use another language to understand meanings in alternative ways. Finally, without a doubt, translation is a great tool.